Economic Analysis of Forest Landscape Restoration Options in Kenya - Cheboiwo, Joshua; Langat, David; Muga, Meshack; Kiprop, Jonah (Kenya Forestry Research Institute, 2016)
Forest and land degradation is a serious global problem worldwide, particularly in developing countries experiencing high population growth and unemployment rates. It is estimated that at global level between 1 billion to over 6 billion ha of the forest landscapes are degraded. The main cause of degradation is through conversions of forests to alternative land uses that has impacted negatively on productivity and diminished the flow of products and services for human well-being. Forest landscape restoration received global endorsement for collective actions to restore health and vitality of degraded landscapes. The decision was informed by the fact that continued environmental degradation will have long term impacts on the overall human wellbeing hence the need to undertake some initiatives to address and minimize the impacts. Through the Bonn Challenge the global community has pledged to restore 150 million hectares of the world’s deforested and degraded land by 2020, and 350 million hectares by 2030 (www.bonnchallenge.org/content/challenge). Underlying the Bonn Challenge is the Forest and Landscape Restoration (FLR) approach, which aims to restore ecological integrity and improve human well-being through multifunctional landscapes. The Bonn Challenge is a practical method of realizing many existing international commitments, including the CBD Aichi Target 15, the UNFCCC REDD+ goal, and the Rio+20 land degradation neutrality goal. As part of its contribution to the global effort to mitigate climate change, the Africa Continent through AFRA A100 pledged 100 million hectares. Kenyan government has pledged to restoration and reforestation of 5.1 million hectares by 2030 as part of its commitment to global Forest Landscape restoration. However, forest restoration involves investments whereas the costs and benefits of undertaking such massive project are yet to be defined in monetary terms. However, forest restoration involves investments and the costs and benefits of massive planned landscape restorations are yet to be defined in monetary terms. Therefore, access on likely costs and benefits of restoration efforts is crucial to inform all stakeholders on the best bet for achieving restoration goals. To address the data and information gaps, it is critical to quantify the likely benefits and costs of various interventions over wide range of landscapes. Economic analysis will help justify and support resource mobilization for the national forest landscape restoration targets. In addition, the analysis will quantify and identify the best options for achieving both short and long term benefits to landowners and stakeholders at national, regional and global levels. To contribute to Kenya government commitments to the Bonn Challenge and to actualize the national restoration strategy, economic analysis of restoration options was mooted to provide a comprehensive report.
Keywords: FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry; Kenya